1977
DOI: 10.1021/ja00444a022
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity and conjugation

Abstract: A new approach to aromaticity of conjugated hydrocarbons is described. It is based on the concept of conjugated circuits, which has been recently recognized as an essential structural element for characterization of conjugated systems (Chem. Phys. Lett., 38, 68 (1976)). Kekulé structures of a conjugated hydrocarbon are examined and circuits with an alternation of CC double and single bonds enumerated. Systems having only (4 + 2) conjugated circuits are defined as aromatic. Systems having only 4n conjugated cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
219
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(232 citation statements)
references
References 7 publications
11
219
0
2
Order By: Relevance
“…77,78; and with different physical consequences -as in Refs. [38][39][40]62,[79][80][81]38. On the other hand, from a molecular-orbital perspective, there are relevant spanning subgraphs (identified with Sachs subgraphs, 23 supplemented with single-site components to make the result spanning), for which forcing ideas might somehow also be relevant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…77,78; and with different physical consequences -as in Refs. [38][39][40]62,[79][80][81]38. On the other hand, from a molecular-orbital perspective, there are relevant spanning subgraphs (identified with Sachs subgraphs, 23 supplemented with single-site components to make the result spanning), for which forcing ideas might somehow also be relevant.…”
Section: Resultsmentioning
confidence: 99%
“…It is realized that e is chemically relevant in Pauling's work, 35,36 and C is relevant in "conjugated-circuits" theory. [37][38][39][40][41][42][43] Next, our initial view of "forcing" is indicated. 6 S of conjugated 6-cycles of G is 6-forcing if no other Kekule structure κ of G manifests the same subset of conjugated 6-cycles with the same conjugation pattern within each of these cycles.…”
Section: Forcing For Kekule Structuresmentioning
confidence: 99%
“…In the quantitative evaluation of aromaticity, experimentally determined or theoretically calculated, parameters currently used include: magnetic properties, 2-12 geometry, [13][14][15][16][17][18] bond orders, [19][20][21][22][23][24][25][26][27][28] isodesmic energy, 29 combustion energy, 30 (topological) resonance energy, [31][32][33][34][35][36][37][38] bond lengths [40][41][42][43][44][45][46] etc.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] Almost simultaneously, "topological resonance energy" TRE was put forward by Aihara 31 and Gutman et al 32 The values of aromaticity (Randić) and TRE (Gutman) are computed using very different formulas. These two models, used in the quantitative computation of aromaticity, use the "limit" Kekulé structures, in fact non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of k-resonance originates from Clar's aromatic sextet theory [3] and Randić's conjugated circuit model [18,19,20]. In the former Clar found that various electronic properties of polycyclic aromatic hydrocarbons can be predicted by defining mutually resonant sextets [7] (i.e., disjoint hexagons that are all alternating with respect to a Kekulé structure).…”
Section: Introductionmentioning
confidence: 99%